Hsp12p and PAU genes are involved in ecological interactions between natural yeast strains. (30th July 2015) - Rivero, Damaríz; Berná, Luisa; Stefanini, Irene; Baruffini, Enrico; Bergerat, Agnes; Csikász‐Nagy, Attila; De Filippo, Carlotta; Cavalieri, Duccio
Summary The coexistence of different yeasts in a single vineyard raises the question on how they communicate and why slow growers are not competed out. Genetically modified laboratory strains of Saccharomyces cerevisiae are extensively used to investigate ecological interactions, but little is known about the genes regulating cooperation and competition in ecologically relevant settings. Here, we present evidences of Hsp12p‐dependent altruistic and contact‐dependent competitive interactions between two natural yeast isolates. Hsp12p is released during cell death for public benefit by a fast‐growing strain that also produces a killer toxin to inhibit growth of a slow grower that can enjoy the benefits of released Hsp12p. We also show that the protein Pau5p is essential in the defense against the killer effect. Our results demonstrate that the combined action of Hsp12p, Pau5p and a killer toxin is sufficient to steer a yeast community.